Complete Chloroplast Genomes and Comparative Analyses of Three Paraphalaenopsis (Aeridinae, Orchidaceae) Species - Chen, Jinliao; Wang, Fei; Zhao, Zhuang; Li, Minghe; Liu, Zhongjian; Peng, Donghui (International journal of molecular sciences, 2023)
Paraphalaenopsis, a genus of perennial herbs from the family Orchidaceae, contains a number of ornamental species. However, there is no information on the chloroplast genomes of Paraphalaenopsis, which limits our studies of this genus. In this study, we reported the chloroplast genomes of three species of Paraphalaenopsis (P. labukensis, P. denevel, and P. laycockii ‘Semi-alba’) and performed comprehensive comparative analysis. These three chloroplast genomes showed a typical quadripartile structure. Their lengths ranged from 147,311 bp to 149,240 bp. Each genome contained 120 unique genes, including 74 protein-coding genes, 38 tRNA genes, and 8 rRNA genes. Comparative analysis revealed major differences in sequence divergence in the three chloroplast genomes. In addition, six hypervariable regions were identified (psbM-trnDGUC, psbB, ccsA, trnKUUU, trnSGCU-trnGUCC, rps16-trnQUUG) that can be used as DNA molecular markers. Phylogenetic relationships were determined using the chloroplast genomes of 28 species from 12 genera of Aeridinae. Results suggested that Paraphalaenopsis was a clade of Aeridinae that was sister to the Holcoglossum-Vanda clade, with 100% bootstrap support within Aeridinae. The findings of this study provided the foundation for future studies on the phylogenetic analysis of Aeridinae.